(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
At present, unmanned aerial vehicles (UAVs) are rapidly gaining popularity and are widely employed across various domains, including military, civilian, and scientific fields. Particular attention is given to the development of systems and means of UAV-based complexes, as this represents a key component for the effective utilization and integration of UAVs in diverse tasks. The topic of the prospects for developing systems and means of UAV complexes is highly relevant and attracts interest from a wide range of specialists due to the potential and capabilities they offer. This scientific article examines the main directions and challenges in the development of systems and means of UAV complexes, as well as analyzes the prospects for their future applications. Significant attention is devoted to analyzing existing problems and their solutions, while various approaches to enhancing the efficiency and functionality of UAV complex systems and means are proposed.